2022
DOI: 10.3389/fgene.2022.965329
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic exosome-related LncRNA risk model correlates with the immune microenvironment in liver cancer

Abstract: Background: Emerging studies have shown the important roles of long noncoding RNAs (lncRNAs) in the occurrence and development of liver cancer. However, the exosome-related lncRNA signature in liver cancer remains to be clarified.Methods: We obtained 371 tumor specimens and 50 normal tissues from the TCGA database. These samples were randomly divided into the training queue and verification queue. The exosome-related lncRNA risk model was verified by correlation analysis, Lasso regression analysis, and Cox reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…63 In a TCGA analysis from 371 HCC samples, 5 exosome-related lncRNA were associated with poor outcome and also related to overexpressed immune checkpoints. 64 This lncRNA-exosomal signature may help to propose an adapted and personalised immunotherapy for each HCC patient. Interestingly, one of these lncRNA, muskelin 1 antisense RNA (MKLN1-AS), was shown to promote tumour growth 65 or drive EMT of liver cancer cells.…”
Section: The Role Of Non-coding Rnas In Controlling Lpc Transformatio...mentioning
confidence: 99%
“…63 In a TCGA analysis from 371 HCC samples, 5 exosome-related lncRNA were associated with poor outcome and also related to overexpressed immune checkpoints. 64 This lncRNA-exosomal signature may help to propose an adapted and personalised immunotherapy for each HCC patient. Interestingly, one of these lncRNA, muskelin 1 antisense RNA (MKLN1-AS), was shown to promote tumour growth 65 or drive EMT of liver cancer cells.…”
Section: The Role Of Non-coding Rnas In Controlling Lpc Transformatio...mentioning
confidence: 99%
“…From the in silico analysis of human liver cancer tissue datasets, Su et al identified a predictive signature based on five upregulated exosome-related lncRNAs (AC099850.3, LINC01138, MKLN1-AS, AL031985.3, and TMCC1-AS1) which have been associated with poor prognosis in liver cancer patients [111]. In the risk model created by the authors, the signature is correlated with the elevated expression of some crucial regulatory mechanisms of the immune system, and is related to the tumor immune microenvironment [111].…”
Section: Lncrna-extracellular Vesicles As Biomarkers In Hepatocellula...mentioning
confidence: 99%
“…However, previous studies only evaluated the prognosis of OC based on exosome-related genes prediction models (32) and did not integrate the necessary information about exosome lncRNA. Previous studies have demonstrated the effectiveness of exosome-related lncRNA prognostic models in breast cancer (33), esophageal squamous cell carcinoma (34), and hepatocellular carcinoma (35,36). However, their applicability in OC remains uncertain.…”
Section: Introductionmentioning
confidence: 99%